The Working Memory Network and Its Association with Working Memory Performance in Survivors of non-CNS Childhood Cancer. Issue 3 (3rd April 2021) - Siegwart, Valerie; Steiner, Leonie; Pastore-Wapp, Manuela; Benzing, Valentin; Spitzhuttl, Janine; Schmidt, Mirko; Kiefer, Claus; Slavova, Nedelina; Grotzer, Michael; Roebers, Claudia; Steinlin, Maja; Leibundgut, Kurt; et al.
ABSTRACT: Childhood cancer and its treatment puts survivors at risk of low working memory capacity. Working memory represents a core cognitive function, which is crucial in daily life and academic tasks. The aim of this functional MRI (fMRI) study was to examine the working memory network of survivors of childhood cancer without central nervous system (CNS) involvement and its relation to cognitive performance. Thirty survivors (aged 7–16 years, ≥ 1 year after cancer treatment) and 30 healthy controls performed a visuospatial working memory task during MRI, including a low- and a high-demand condition. Working memory performance was assessed using standardized tests outside the scanner. When cognitive demands increased, survivors performed worse than controls and showed evidence for slightly atypical working memory-related activation. The survivor group exhibited hyperactivation in the right-hemispheric superior parietal lobe (SPL) in the high- compared to the low-demand working memory condition, while maintaining their performance levels. Hyperactivation in the right SPL coincided with poorer working memory performance outside the scanner in survivors. Even in survivors of childhood cancer without CNS involvement, we find neural markers pointing toward late effects in the cerebral working memory network. Abbreviations fMRI: Functional magnetic resonance imaging; CNS: Central nervous system; MNI: Montreal Neurological Institute; SES: Socioeconomic status; SPL: Superior parietal lobe